Analisis Pengaruh Hilirisasi dan Faktor-Faktor Lainnya Terhadap Ekspor LNG Indonesia - Wigati, Lintang; Utami, Efri Diah (Seminar Nasional Official Statistics, 2024)
Beginning in 2010, downstreaming decreased the volume of LNG exports while increasing their value. As one of the six largest LNG exporting countries in 2022, Indonesia has the lowest export value, which should increase after downstreaming. Therefore, the impact of downstreaming and other factors on the value of Indonesian LNG exports will be explored. The study used descriptive analysis and Error Correction Mechanism (ECM). The average value of LNG exports after downstreaming has gone up. The value of LNG exports is positively correlated with mining and quarrying GDP and exchange rate; however, world LNG prices are adversely associated. According to ECM, downstreaming only has a long-term impact on Indonesia's LNG export value. The value of Indonesian LNG exports is influenced by the exchange rate, world LNG prices, and mining and quarrying GDP in both the short and long term. Downstreaming can continue, enhancing the value of Indonesian LNG exports.